"When the Music's Over" then "Dancing with a Partner Will Help You Find the Beat". (October 2021) - Gillett, Grant; Butler, Mary
Abstract: Responses to brain injury sit in the intersection between neuroscience and an ethic of care, and require sensitive and dynamic indicators of how an individual with brain injury can learn how to live in the context of a changing environment and multiple timescales. Therapeutic relationships and rhythms underpinning such a dynamic approach are currently obscured by existing models of brain function. Something older is required and we put forward narrative types articulating outcomes of brain injury over various periods and starting points in time. Such storytelling challenges a static neuropsychological paradigm and moves from an ethics that focuses on patient autonomy into one that is reflective of the cognitive supports and therapeutic relationships that underpin ways that the patient can re-find the beat that proves the music is not over.